Radical Unilateral Mastectomy for Fibrosed Gangrenous Udder in a Lactating Goat - Kumar, Satveer; Saini, R; Sharma, SK (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Mastitis reflects the inflammation of the mammary gland, which may occur due to any bacterial infection  secondary to teat injury or poor management (Marogna et al.,  2010). Radical mastectomy (unilateral or bilateral) is a salvage  procedure and indicated in cases of chronic suppurative  mastitis, gangrenous mastitis and neoplastic or hyperplastic  conditions of the udder (Andreasen et al., 1993; El-Maghraby,  2001; Canle et al., 2004). Gangrenous mastitis is a peracute  form of mastitis, characterized by necrosis of the udder tissue,  caused by alpha-toxins (Smith and Sherman, 2009). Physical  examination of the udder is characterized by discolored  (blue- blackish or blue-greenish) and cold udder (Ribeiro et al., 2007). Gangrenous mastitis is one of the most difficult forms  of mastitis to be treated (Bloway, 1993), and in very severe  cases, gangrene may lead to toxemia and loss of animal life  (Ribeiro et al., 2007). Unilateral or bilateral mastectomy is  recommended as a pain-relieving procedure for extensive  lesions involving udder and in cases of chronic mastitis,  gangrenous lesions, or neoplasia (Canle et al., 2004). The  present case report describes unilateral mastectomy for the  management of incurable extensive fibrosis of udder while  allowing the other mammary gland to continue lactation.
Keywords: Gangrene; Goat; Laceration; Mastectomy; Mastitis; Udder